Investigating The Role of Key Opinion Leaders, Marketing Content and User Experience on Purchase Intention of Eco-Friendly Products Among Gen Z - Juwita, Isna; Wandanaya, Anita Bawaiqki; Akhirianto, Pas Mahyu; Kushariyadi, Kushariyadi; Violin, Vivid; Mustafa, Fahrina (Journal of Social Science and Business Studies, 2025)
Environmental concerns are carried out comprehensively, not only centered on the production process, regulation making and consumption styles, but attention and focus on the impacts or consequences that will be caused in the long term also forces each party to care about environmental issues. There are three important factors in influencing the purchase intention of eco-friendly products, especially for generation Z, namely key opinion leaders, marketing content and user experience. This study aims to analyze the influence of the three independent variables, namely key opinion leaders, marketing content and user experience on the purchase intention of eco-friendly products. This study uses a qualitative method, namely by collecting and reviewing various literature that discusses the influence of key opinion leaders, marketing content and user experience on interest in buying eco-friendly products. Based on the results of the analysis of previous literature that examines and concludes the relationship and influence of key opinion leaders, marketing content and user experience on the purchase intention of eco-friendly products, it is concluded that all predictor variables have a close relationship and can positively influence the purchase intention of eco-friendly products.